PEMBERDAYAAN PETANI NANAS BERBASIS POTENSI LOKAL LAHAN GAMBUT DI DESA TANJUNG LEBAN KECAMATAN BANDAR LAKSAMANA KABUPATEN BENGKALIS - Teddy Kurniawan; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
TanjungLeban Village is an area where almost the entire area is peatland. The research was conducted in TanjungLeban Village, Bandar Laksamana District, Bengkalis Regency. The people of TanjungLeban village use peatlands to grow pineapples. With the aim of knowing, describing and analyzing how empowerment, the results of empowerment and analyzing factors that can improve pineapple farmers based on local potential of peatlands. This study uses a descriptive qualitative research method. Data collection was carried out in this study in the form of direct observation, in-depth interviews, and documentation. The results of the research are in accordance with the analysis showing that the indicator of empowerment that has not run optimally is sustainability. For other empowerment indicators run optimally. The supporting factors for pineapple farmers are mindset and creativity as well as pineapple farmer innovation. The obstacle factor experienced by pineapple farmers is the lack of marketing and market networks, pests found on pineapple fields Keywords: Empowerment, Pineapple Farmer, Peatlands